Assessing the Capacity of the US Health Care System to Use Additional Mechanical Ventilators During a Large-Scale Public Health Emergency. (9th October 2015) - Ajao, Adebola; Nystrom, Scott V.; Koonin, Lisa M.; Patel, Anita; Howell, David R.; Baccam, Prasith; Lant, Tim; Malatino, Eileen; Chamberlin, Margaret; Meltzer, Martin I.
Abstract: Objective: A large-scale public health emergency, such as a severe influenza pandemic, can generate large numbers of critically ill patients in a short time. We modeled the number of mechanical ventilators that could be used in addition to the number of hospital-based ventilators currently in use. Methods: We identified key components of the health care system needed to deliver ventilation therapy, quantified the maximum number of additional ventilators that each key component could support at various capacity levels (ie, conventional, contingency, and crisis), and determined the constraining key component at each capacity level. Results: Our study results showed that US hospitals could absorb between 26, 200 and 56, 300 additional ventilators at the peak of a national influenza pandemic outbreak with robust pre-pandemic planning. Conclusions: The current US health care system may have limited capacity to use additional mechanical ventilators during a large-scale public health emergency. Emergency planners need to understand their health care systems' capability to absorb additional resources and expand care. This methodology could be adapted by emergency planners to determine stockpiling goals for critical resources or to identify alternatives to manage overwhelming critical care need. ( Disaster Med Public Health Preparedness . 2015;9:634–641)